A realistic assessment of COVID-19 vaccination’s effect on the Malaysian stock market’s downside risk / Ahmad Fauze Abdul Hamit ... [et al.] - Abdul Hamit, Ahmad Fauze; Othman, Maryam Qaameelah; Fridrict, Ninalyn; Mohd Fikri Lai, Abdul Aziz Lai (Universiti Teknologi MARA Selangor, 2023)
Numerous studies have revealed the devastating negative impact of the global-scale widespread coronavirus disease (COVID-19) pandemic on the economy, especially on the development of the stock market. Despite countries' efforts, such as implementing movement restriction orders to control the spread of the deadly virus, it has only exacerbated the economic difficulties. This research aims to provide a realistic assessment of the economic impact of vaccinations in mitigating the systemic risk that could hurt the stock market. We scrutinise the daily time series data of the Kuala Lumpur Composite Index from 19 th February 2020 to 2 nd March 2022 (500 trading days). We find a positive relationship between COVID-19 daily new cases, vaccination rates, investor sentiment, and the stringency index towards the Value-at-Risk in the Malaysian stock market. Statistically, with every 1% increase in COVID-19 daily new cases, Malaysia's stock market risk increases by 14.33%. Additionally, for every 1% increase in vaccine doses administered, Malaysia's stock market risk also increases by 3.42%. On the other hand, higher investor sentiment, proxied by trading volumes, and rigorous government intervention, proxied by the stringency index, are associated with higher market risk and uncertainty by 7.09% and 13.19%, respectively. The current study's findings significantly impact many aspects, including the body of knowledge, policymakers, and the institutional and individual investors community.